Ganoderma lucidum spore powder alleviates rheumatoid arthritis-associated pain hypersensitivity through inhibiting accumulation, N1 polarization, and ROS production of neutrophils in mice - Huang, Sen; Zhan, Zhaochun; Xu, Fei; Liu, Xiaolin; Fang, Zhenning; Wu, Wenbo; Liang, Zhile; Liu, Guoguo; Wang, Mengyuan; da Silva, Helena Soares; Luo, Xin; Mo, Kai (Frontiers in Immunology, 2025)
IntroductionRheumatoid arthritis (RA) is a chronic condition characterized by joint pain that significantly impairs patients’ work and daily lives. The limited understanding of the pathological mechanisms underlying RA-related pain poses challenges for effective clinical pain management. Ganoderma lucidum spore powder (GLSP) has demonstrated therapeutic benefits in various diseases, with no reported toxicity or adverse effects.MethodsThis study investigates the role of neutrophils in the pathological mechanisms of RA-related pain using collagen-induced arthritis (CIA) mice and an ex vivo neutrophil model. A combination of techniques, including animal models, flow cytometry, behavioral testing, cell adoptive transfer, and network pharmacology analysis, was employed to evaluate the effects and targets of GLSP on pain symptoms and neutrophil activity in CIA mice.ResultsFlow cytometric analysis revealed the accumulation and activation of neutrophils in the paws of CIA mice. Furthermore, the levels of pro-inflammatory CD95+ neutrophil subpopulations (N1 state) and ROS+ cells in the affected paws were positively correlated with the severity of mechanical allodynia and heat hyperalgesia observed in these mice. Our findings indicate that oral administration of GLSP significantly alleviates joint destruction, paw swelling, and pain hypersensitivity in CIA mice. Notably, GLSP reversed CIA-induced neutrophil accumulation, N1 polarization, and reactive oxygen species (ROS) production. Both network pharmacology target prediction and in vivo/in vitro experimental validation indicated that GLSP inhibits N1 polarization and ROS production in neutrophils by modulating the TNF-α signaling pathway, thus exerting RA-specific analgesic effects.DiscussionIn summary, this study offers new insights into the pathological mechanisms of RA-related pain and demonstrates that neutrophil accumulation, N1 polarization, and ROS production contribute to RA-related pain. GLSP alleviates RA-related pain by inhibiting the pro-inflammatory phenotype of neutrophils, highlighting its potential for clinical translation in the treatment of RA.